Bangladesh : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria-Staff Report, Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Bangladesh. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
Bangladesh has made substantial progress in strengthening macroeconomic conditions and structural policies. Strong vigilance, guided by adherence to programmed deficit targets, is needed, however. The strengthening of debt management practices now under way will reinforce debt sustainability. Restrained monetary policy has brought down inflationary pressures and supported the rebuilding of reserves, and there is a need for regulatory reforms to address vulnerabilities in the banking system. A comprehensive review of foreign exchange regulations would provide a firm guide to increase the attractiveness of Bangladesh to foreign direct investment (FDI) and portfolio investment flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet